Optimized Scheduling of Integrated Energy Systems Considering Electric Vehicles and Carbon Emission Trading - Yanhong Xiao; Bin Qian; Jiaxiang Ou; Weibin Lin; Houpeng Hu; Xiaoming Lin; Yuedan Deng; Jianlin Tang (IEEE Access)
This study proposes an optimized dispatch model for integrated energy systems (IES) incorporating electric vehicles (EVs) and carbon emission trading (CET) to analyze their dynamic interactions. The model aims to minimize IES operating costs by systematically evaluating the impacts of EV penetration levels and CET parameters on economic and environmental performance. Methodologically, Monte Carlo simulations characterize stochastic EV behaviors, a stepwise CET mechanism is developed with emission thresholds, and piecewise linearization combined with convex relaxation transforms nonlinear constraints into tractable formulations. The YALMIP/GUROBI solver is employed to compare eight dispatch scenarios. Key results demonstrate that integrating EVs with carbon capture under CET reduces operating costs by 7.64% and emissions by 17.68%. System emissions exhibit a U-shaped relationship with EV penetration, reaching a minimum at 9.20%. Maximum emission reductions from EV charging optimization occur when CET prices range 250-300 CNY/ton and EV penetration spans 12.31%-19.43%, providing critical thresholds for policy design.